STRATEGI PARTAI KEADILAN SEJAHTERA (PKS) DALAM MEMENANGKAN PASANGAN MOHAMAD IDRIS ABDUL SHOMAD DAN IMAM BUDI HARTONO PADA PILKADA KOTA DEPOK 2020 - Roro Ajeng Kusumandari (2022)
This study aims to determine the Partai Keadilan Sejahtera (PKS) strategy in winning candidate Mohammad Idris Abdul Shomad and Imam Budi Hartono. Political parties have a very big role in the election, as participation and winning the candidate. Political strategy how to be winner in the election, the basic concept of political strategy Peter Schroder's theory. This research focus on strategy PKS in the Depok Local election 2020 that was used descriptive qualitative research method with primary and secondary data sources. Data collection techniques are interview and literature studies in the form of books, news, and previous research journals that are relevant on this research. There is varying of strategy in the Depok local election to expand and maintain a support candidate in the election. The winner depok local election 2020 is Mohammad Idris Abdul Shomad-Imam Budi Hartono bring domination PKS in Depok City. Strategy ofensif and strategy defensif theory will be used to describe mobilization voters. The result show that PKS and Idris-Imam success team used strategy such as the P4otang, door to door campaign, and offline campaign.